PENGEMBANGAN HORTIKULTURA DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DESA PANA KECAMATAN ALLA KABUPATEN ENREKANG - Erna Pasanda; Bertha Beloan; F.X. Resky Randa; A. G. Patinggi; R. I. Pabutungan; Zeptian Zeptian (Gapenas Publisher, 2021)
This service activity aims to increase people's income through the development of horticultural crops, especially spinach, long beans and chicory. The activity was carried out by 6 students and lecturers of the Indonesian Christian University Paulus. The program of activities was carried out in Pana Village, Alla District, Enrekang Regency. The technique of implementing service activities includes making gardens around the community's home yards including community preparation, nurseries, land preparation, planting and fertilizing plants. The results of the activities achieved include the availability of vegetables for the participants to consume and some can be sold to the nearest market